2014
DOI: 10.1016/j.jcf.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ivacaftor in patients with cystic fibrosis and a non-G551D gating mutation

Abstract: Ivacaftor was efficacious in a group of patients with CF who had selected non-G551D gating mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
295
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(318 citation statements)
references
References 19 publications
18
295
2
3
Order By: Relevance
“…9 Diagnosis can also be established on CFTR mutation testing, although, because of the large number of mutations, a negative test cannot rule out the diagnosis unless the entire CFTR gene has been sequenced; this is rarely employed as a first-line diagnostic tool and is reserved for difficult diagnoses. However, whereas previously it may have been sufficient to secure a diagnosis on the basis of a sweat test, with the recent development of mutation-specific small-molecule treatments, 10 it is becoming increasingly necessary for a patient's mutation(s) to be defined.…”
Section: Clinical Presentation Diagnosis and Disease Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Diagnosis can also be established on CFTR mutation testing, although, because of the large number of mutations, a negative test cannot rule out the diagnosis unless the entire CFTR gene has been sequenced; this is rarely employed as a first-line diagnostic tool and is reserved for difficult diagnoses. However, whereas previously it may have been sufficient to secure a diagnosis on the basis of a sweat test, with the recent development of mutation-specific small-molecule treatments, 10 it is becoming increasingly necessary for a patient's mutation(s) to be defined.…”
Section: Clinical Presentation Diagnosis and Disease Manifestationmentioning
confidence: 99%
“…Twice-daily oral administration in patients with a G551D mutation led to a 10% absolute improvement in FEV 1 , a reduction in pulmonary exacerbations and improved quality-of-life scores; additionally, it seemed to have benefits outside the lungs, with improvement in weight and body mass index (BMI) thought to be related to gut bicarbonate secretion. It was initially licensed (and is now available in the UK) for patients with the G551D mutation, but a subsequent trial demonstrated similar benefit for the small group of patients with other class III mutations, 10 for which the drug has now also been licensed and is awaiting funding approval. Furthermore, a trial in patients with the class IV mutation R117H (NCT01614457), which demonstrated smaller benefits, has led, to date, to the US Food and Drug Administration approval and is being considered by the European Medicines Agency.…”
Section: Treatments For Class III Mutationsmentioning
confidence: 99%
“…Trials confirmed efficacy in Asp551Gly (G551D) the commonest mutation in this class (7,8) and subsequently in rarer gating mutations (9). Significant improvements in FEV 1 , exacerbation rate, weight and health-related quality of life led to ivacaftor being licensed for use in these patients aged 6 years and above; long term follow up demonstrates a slowing in the rate of decline of lung function, confirming true disease 'modulation'.…”
Section: Potentiatorsmentioning
confidence: 92%
“…Reductions were also seen in pulmonary exacerbations, patient-reported respiratory symptoms, and concentration of sweat chloride (2), and children aged 6-11 years with a G551D mutation also experienced improvements with ivacaftor in pulmonary function, weight, and CFTR activity (29). Additional work demonstrated significant improvements in lung function, body mass index, sweat chloride, and CF quality-of-life scores in patients with a non-G551D gating mutation (30), although marginal effects were seen in those with the class IV altered conductance mutation R117H (31). Assessments of physiological effects of ivacaftor postapproval note that ivacaftor restores mucociliary clearance, normalizes duodenal pH, and has been associated with a reduction in culturing P. aeruginosa in patients with G551D mutations (32,33).…”
Section: Cftr-based Therapeutic Approachesmentioning
confidence: 99%